Analisis Capaian Pembangunan SDM dan Faktor-faktor Pendorong Penyerapan Tenaga Kerja di Provinsi Bali - Theresia Mutiara Galistya (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
Human resource development in the Bali Province can be illustrated through the development of the Human Development Index (HDI) achievements and employment conditions. Until 2018, HDI of Bali Province recorded continued to grow and is at a "high" level. The challenge that arises is that there are still gaps in the achievement of HDI at the regency level. Efforts to increase the Mean Years of Schooling (RLS) and per capita expenditure in regency with a "moderate" HDI status seem to be one solution to narrowing disparities in human resource development between regions. In view of employment conditions, Bali's Open Unemployment Rate (TPT) was recorded to be the lowest nationally. However, the low level of education possessed by most workers has an impact on the low wages or salaries that can be obtained. The study was complemented by causal analysis to see the effect of economic growth, investment, and the Provincial Minimum Wage (UMP) on employment in the Bali Province. Case studies are conducted according to data conditions that released by Statistics Indonesia for 2009-2017. The results showed that simultaneously all three variables had a close relationship with employment. This is indicated by the R2 value that recorded at 94,3 percent. Partially, economic growth has a positive effect on employment though not significant. Investment and UMP variables have a positive and significant effect on employment in the Bali Province.